Onion Price Prediction Based on Artificial Intelligence - R, Nalini; K, Sountharya; R, Vishnu Priya; R.V., Punitha (International Research Journal of Multidisciplinary Technovation, 2020)
India being a horticulture nation, its economy prevalently relies upon horticulture yield development and agroindustry items. Information Mining is a developing examination field in onion yield investigation. Yield forecast is a significant issue in horticultural. Any rancher is keen on knowing how a lot yield he is going to anticipate. Break down the different related properties like area, pH esteem from which alkalinity of the dirt is decided. Alongside it, level of supplements like Nitrogen (N), Phosphorous (P), and Potassium (K) Location is utilized along with the utilization of outsider applications like APIs for climate and temperature, sort of soil, supplement estimation of the dirt in that locale, measure of precipitation in the district, soil organization can be decided. Every one of these traits of information will be examined, train the information with different appropriate AI calculations for making a model. The framework accompanies a model to be exact what’s more, exact in foreseeing onion yield and convey the end client with appropriate proposals about required manure proportion in light of barometrical and soil parameters of the land which improve to build the harvest yield and increment rancher income.